Socio-Demographic Determinants of Leisure Time Physical Inactivity of Adolescents from the Voivodships of Central Poland - Elżbieta Biernat; Adrian Lubowiecki-Vikuk (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2017)
The aim of the study is to assess the physical leisure time activity among the students of grade I–III of junior high school (aged 13–16) – during the school year and holidays – and identify possible causal factors of physical inactivity in this social group. The relationship between participation in sport for all during the school year (regular, periodic, sporadic) and during holidays (physically active/passive) and socio-demographic variables characterizing the structure was analyzed using the Chi 2 test. The relationship between respondents inactivity and those traits was assessed using log-linear analysis. The higher the grade (especially among girls), the more physically inactive individuals, the number of which grew during the school year as well as during holidays. The risk factors for inactivity included high BMI, living in the countryside and female sex. In case of girls (76.3%) the risk of inactivity increased by almost 1.4 times, as it did (OR = 0.75) with regard to living in rural areas (76.4%). The chance of being active increases more than 3-fold among those with normal BMI (28.0%) and the underweight (29.9%). Adolescents’ inactivity (increasing along with the grade pupils are in) points to the shortcomings of Polish process of education and an urgent need for system-based approach to promote active lifestyle in this social group.